Decision-making frameworks for controversial public decision processes: a comparative analysis with a Case Study - Gonçalves, V. (Dinâmia-CET, Working paper, 2012)
Earlier approaches and most current practices of project evaluation are still driven mainly by technical and economic concerns and do not incorporate environmental and social issues. Therefore, they have failed to account for sustainability concerns in the evaluation of major projects with environmental impacts. In this paper a comparative analysis of three new decision-making frameworks is presented for a more sustainable assessment of these projects. Similarities and differences regarding their theoretical base, objectives overarching issues and operational implementation,are analyzed aiming to reveal the main issues of the evaluation process. A case study is also presented with the critical analysis of the ex-post evaluation process of the Alqueva dam multipurpose project based on the application of the methodological frameworks. The aim is to illustrate the relevance of these methodologies for the improvement of the evaluation process vis à vis more traditional practices.